Religious Images and Urban Places in Vergil’s Aeneid - Cecilia Ames (Mythos, 2021)
Vergil’s Aeneid, written in the Augustan period, when Rome appeared at the height of its urban development and was widely regarded as the city par excellence, powerfully addresses the changes that the space of the city of Rome experienced over time. In the poem, different sites of the city appear modified by many agents who had appropriated, transformed, and crafted them through a range of religious and civic practices. Subtly, Vergil takes the topic of urban development and brings Rome's humble origins and its emblematic places to the memory of his contemporaries, with a strong emphasis on different kinds of religious images and expressions. In this way, the focus on the relationship between Roman religion and urban space allows us to read the Aeneid from a viewpoint that warrants further investigation.